2018
DOI: 10.1177/0021998318765290
|View full text |Cite
|
Sign up to set email alerts
|

High-speed infrared thermal imaging during ballistic impact of triaxially braided composites

Abstract: Ballistic impact experiments were performed on triaxially braided polymer matrix composites to study the heat generated in the material due to projectile velocity and penetration damage. Triaxially braided (0/+60/−60) composite panels were manufactured with T700S standard modulus carbon fiber and two epoxy resins. The PR520 (toughened) and 3502 (untoughened) resin systems were used to make different panels to study the effects of resin properties on temperature rise. The ballistic impact tests were conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…High-Speed Bullet Impact Test. High-speed impact tests are typically performed by a projectile that will be ejected from a high-pressure pneumatic accelerator [33,34]. A similar confguration was used in this study, and a mild steel hemispherical projectile with details is shown in Table 2.…”
Section: Fabrication Of Laminate Bymentioning
confidence: 99%
“…High-Speed Bullet Impact Test. High-speed impact tests are typically performed by a projectile that will be ejected from a high-pressure pneumatic accelerator [33,34]. A similar confguration was used in this study, and a mild steel hemispherical projectile with details is shown in Table 2.…”
Section: Fabrication Of Laminate Bymentioning
confidence: 99%
“…Similar high element erosion values, as well as high SLIM values, have been explained by the fact that the matrix undergoes significant adiabatic heating during large plastic deformations. 15 The resulting softening from this heating results in greater ductility of the composite. Because of the low thermal conductivity of the polymer constituent, even under low-rate loading heating will occur.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, while MAT213 can support rate-dependent behavior, rate dependency was not used in describing the stressstrain relationship due to the lack of experimentally obtained rate dependent data. Second, research 48 has shown that, under impact loading, rise in local temperature around the point of impact can be significant (temperatures exceeding 485 K, well above the respective glass transition temperatures for the polymer constituents). This thermomechanical phenomenon (Taylor-Quinney effect) needs to be incorporated in the FE simulations along with the computation of thermal strains and stresses using temperature-dependent data, if appropriate.…”
Section: Discussionmentioning
confidence: 99%